Dampak Cuaca Terhadap Hasil Produksi Tanaman Bayam Merah Di Kelurahan Fitu Kota Ternate - Eva Marthinu; Dinarta Fajar; Buhari Umasugi; Syarifuddin Adjam (Journal on Education, 2025)
The agricultural sector is a source of life for people who work as farmers. However, changes in weather can threaten crop production, in horticultural crops, namely red spinach plants. This study aims to determine the condition of the weather elements in the Fitu Village, South Ternate City, and the impact of weather changes on the production of red spinach in the Fitu Village, South Ternate City. The research location, in the Fitu Village of South Ternate City from April to May 2023, the method used is qualitative with a descriptive approach. The sampling technique is purposive sampling. Informants selected as many as 15 people, data sources namely primary data and secondary data, data collection techniques using interviews and decommentation. The results of research by farmers in the Fitu Village, on the condition of the weather element that has more influence on plant growth, namely Rainfall, is supported by data (BMKG) Rainfall in 2022 will be in May and December, namely (391.3mm). In 2023 there are January and March (456.1mm). The impact of weather changes that can affect red spinach plants is the attack of pests and diseases that affect production. The production of